Pengaruh Transparansi Zakat, Kualitas Pelayanan, Religiusitas, Terhadap Loyalitas Muzaki dengan Kepuasan dan Kepercayaan Sebagai Variabel Mediasi - Sri, Alda Srilupita (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to look at the effect of zakat transparency, service quality, religiosity on muzakki loyalty with satisfaction and trust as mediating variables in Lembaga Amil Zakat Muhammadiyah West Sumatra Province. This research is a quantitative research. The sample in this study amounted to 200 muzakki from four LazisMu in West Sumatra Province. Data collection techniques using questionnaires. The data were analyzed using SEM-PLS (Structural Equation Model) with the Smart-PLS tool. The results of direct effect testing showed that zakat transparency has a positive and significant effect on the loyalty of muzakki to pay zakat at the Muhammadiyah amil zakat institution in West Sumatra Province. While other variables such as service quality, religiosity have a positive but insignificant effect on the loyalty of muzakki in paying zakat at the Muhammadiyah Amil Zakat Institution of West Sumatra Province. While the test results of indirect effects show the quality of service to loyalty through muzakki satisfaction in paying zakat. Transparency of zakat to muzakki loyalty through satisfaction in paying zakat. While religiosity has a positive but insignificant effect on the loyalty of muzakki either directly or with the influence of mediation. Meanwhile, for the mediation test, satisfaction has a positive and significant effect on muzakki loyalty. While trust has a positive but insignificant effect on muzakki loyalty.